The sound of salts by Broadband Acoustic Resonance Dissolution Spectroscopy. (February 2019) - van Ruth, Saskia; Dekker, Pieter; Brouwer, Erwin; Rozijn, Maikel; Erasmus, Sara; Fitzpatrick, Dara
Abstract: Salts are available in different grades and in a wide price range. Some contain more impurities than others, while some have special culinary traits that determine their identity. Acoustic profiling, which is based on the 'hot chocolate effect', may provide an interesting strategy to characterise salts of various origins to underpin their identity. In this study, the link between the identity of 60 food grade and technical salts and their acoustic properties was examined by Broad Acoustic Resonance Dissolution Spectroscopy. In particular, the influence of the composition of the salts and the impact of the salts' particle size distributions on their acoustic profiles were examined. Sodium and potassium contents were measured by flame photometry and the salts' particle size distributions by laser light diffraction. Reference salts (NaCl, KCl, MgCl2 ) and mixtures thereof were analysed for comparison, as well as intact and ground versions of the salt samples. The results show that both the composition and morphology of the salt crystals determine the down-slope of the resonance frequency, which is caused by the rate of release of entrained and dissolved gas. Coarse salts with high levels of non-NaCl constituents showed a rapid decline in sound frequency, which corresponds to a high gas release rate. On the other hand fine salts composed of pure NaCl revealed a slower change in sound frequency and thus lower gas release rates. The frequency minimums were however not affected by the salts' compositions nor particle size distributions. It is primarily the particle size distribution that affects the rate at which gas is released, and thus the change in sound frequency. Only when the particles are more similar in size, the composition also starts playing a role. Since both particle size distribution and composition is unique for each salt, the various salts show distinct acoustic profiles. Evidently, the current study shows that 'listening' to the sound of salts reveals interesting information about their identity and origin. Graphical abstract: Unlabelled Image Highlights: The acoustic profiles of various food and technical grade salts were determined. Salt composition and morphology affected the acoustic traits of the salts. NaCl, KCl and non-NaCl components influenced the gas volumes released. Coarse salts had a different sound frequency curve than fine salts. BARDS is an effective tool for salt profiling and identification.